124 Administration of Fascia Iliaca Block to Patients Who Have Suffered a Neck of Femur Fracture. (28th February 2022) - West, C.; Wright, C.
Abstract: Aim: Hip fractures are the most common serious injury affecting elderly people and are associated with a total cost to the health and social services over £1 billion per year. This injury takes approximately 1% of the NHS budget. Furthermore current 30-day mortality rate is 6.5% so has serious implications for patients. NICE recommend that nerve blocks should be used to help perioperative pain and limit the use of opioids. We audited our use of analgesia, especially fascia iliaca blocks (FIB), to see whether training could improve the management of these patients. Method: We conducted a retrospective cohort study in which a total of 188 patients, who had sustained a hip fracture, were audited during 4 discrete periods between March 2021-July 2021. The primary outcome assessed was whether they had received a FIB preoperatively. Improvements were implemented between audit cycles to see if they achieved desired outcomes. Results: Implementation of good quality teaching to orthopaedic juniors and emergency department registrars and juniors successfully improved rate of FIB from 2.5% to 47%. The rate of FIB was not sustained over time and declined to 22%. Factors thought to influence this decline included regular rotation of junior doctors and increasing time pressures in the emergency department. Conclusions: Our data suggested that low rates of FIB resulted in high opioid use in the emergency department. Allocated teaching sessions on administration of FIB were a successful way to improve use of blocks and reduce opioid use.